1992
DOI: 10.1063/1.351744
|View full text |Cite
|
Sign up to set email alerts
|

Thin film reaction kinetics of niobium/aluminum multilayers

Abstract: Phase formation kinetics in Nb/Al multilayered thin films having overall compositions of 25, 33, 50, and 75 at. % Al have been investigated using scanning calorimetry, x-ray diffraction, and cross-sectional transmission electron microscopy. The first phase to form upon annealing the Nb/Al layered structure of all samples is the NbAls intermetallic. Calorimetry clearly identifies the NbAls formation to be a two-stage process. The first stage is the formation of a planar layer by nucleation and growth to coalesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
1
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 20 publications
7
33
1
1
Order By: Relevance
“…These models are based on different approximations and different phenomena. However, all of the models consider the diffusion along the interfaces and they conclude that the product phase should reach a stationary thickness that depends on the kinetics parameters, in accordance with the experimental results [14][15][16][17]19]. The models also led to a relatively similar particle shape.…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…These models are based on different approximations and different phenomena. However, all of the models consider the diffusion along the interfaces and they conclude that the product phase should reach a stationary thickness that depends on the kinetics parameters, in accordance with the experimental results [14][15][16][17]19]. The models also led to a relatively similar particle shape.…”
Section: Introductionsupporting
confidence: 76%
“…Several experimental studies [14][15][16][17][18][19] reported the presence of a discontinuous phase as the first results of the reaction between the two other phases. However, the entire particle shape has not been reported; thus, it is not possible to compare these experimental results with existing models [13,20,22,23].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…They reported that the growth of the intermetallic CuMg 2 phase takes place in two well separated stages: nucleation and lateral growth of the intermetallic along the interface until coalescence is complete, followed by a diffusion limited vertical growth of the same intermetallic phase. A similar behavior has been observed in other multilayer systems such as Al/ Ni, 11,15 Al/ Nb, 9,16,17 Al/ Ag, 18 Al/ Co, 3 Ni/ Si, 7,16 V / Si, 19 or Cu/ Sn. 20 Coffey et al 16 developed a kinetic model that incorporates the two stage model and allowed the simulation of the corresponding calorimetric traces.…”
Section: Introductionsupporting
confidence: 56%
“…No signature of preferential orientation of the RuSi phase was observed in the pole figures. This twostage silicide reaction phenomenon could be understood after Coffey et al 28 The first stage between 439 °C < T < 524 °C in fig. 2 could be interpreted as the nucleation and lateral growth of a very thin layer of the RuSi phase in the plane of the substrate.…”
Section: A Controlling Pinhole Density With Choice Of Barrier Layermentioning
confidence: 99%